Conversation as educational research. Issue 6 (12th May 2019) - Bojesen, Emile
Abstract: This article introduces a form of 'conversation' distinct from dialogue or dialectic to the context of educational theory, practice, and research. Through an engagement with the thought of Maurice Blanchot, this paper outlines the conditions he attributes to conversation in the form of plural speech, its relationship to research, how it can be educational, and speculatively concludes by considering how it can operate productively within and around educational institutions. As such, this paper provides an original intervention into educational philosophy and theory, which relies on a close reading of key sections of Blanchot's The Infinite Conversation, and reflections on the distinctiveness of his argument in relation to contemporary theoretical approaches, as well as the significance of his thought and its application here to the broader questions of what non-prescriptive theory might have to offer educational research and practice.